Comparison between Camberwell Family Interview and Expressed Emotion Scale in Determining Emotions of Caregivers of Schizophrenic Patients - KUŞCU, MEHMET KEMAL (GALENOS YAYINCILIK, 2013)
Introduction: The aim of the study was to compare the Camberwell Family Interview (CFI) and the Expressed Emotion Scale (EES) in determining the level of expressed emotion in caregivers of patients with schizophrenia. Methods: The study sample included caregivers of 22 schizophrenic patients followed in two psychiatric clinics. The level of expressed emotion in the caregivers was assessed by the CFI and the EES. CFI was applied to caregivers of the inpatients and the procedure was audio recorded. These records were later used for the ratings. EES was completed by the caregivers. Total EES scores were used to determine the level of expressed emotion in the caregivers. Results: Forty point nine percent and 50% of the caregivers had high level of expressed emotion based on the analysis of the data obtained from the CFI and EES. Fifty-nine percent and 50% of the caregivers had low level of expressed emotion based on the data obtained from the CFI and EES. The proportion of the caregivers with high level of expressed emotion as measured by the CFI and the EES were not statistically significantly different within the sample (chi(2)=0.727). Conclusion: The CFI and the EES were similar in determining the level of expressed emotion in caregivers of schizophrenic patients. It can be suggested that the EES, a user friendly tool, may be preferred to determine the level of expressed emotion in caregivers of patients with schizophrenia. However, further studies with larger samples are needed to obtain more reliable results.
Keywords: Schizophrenia; caregivers; expressed emotion; Expressed Emotion Scale; Canberwell Family Interview; CLINICAL-OUTCOMES; RELATIVES; RELAPSE; JAPAN